Perancangan Filter Bandpass dengan Teknik Penggabungan Filter Lowpass dan Highpass - Farida, Fitri; Setijadi, Eko (Fakultas Teknik Universitas Maritim Raja Ali Haji, 2018)
UWB technology started to become an attraction in the field of research since the Federal Communications Commission (FCC) allowing this communication is used for commercial communications at a frequency (3.1 GHz - 10.6 GHz). UWB has a very wide frequency range so that in practice there is often interference due to signal interference. Therefore in UWB system filter design is required to maintain UWB device. In telecommunications, filter is a transmission device that has the function to pass the desired frequency. In this paper designed bandpass filter which is applied for UWB technology. The designed bandpass filter is a combination of a lowpass filter (LPF) and a highpass filter (HPF). The lowpass filter has the characteristic of passing a frequency lower than its cut-off frequency. The highpass filter has the characteristic passing a frequency higher than its cut-off frequency. Considering the characteristics of both filters, the bandpass filter (BPF) is a combination of lowpass and highpass filters. In this research designed lowpass filter in microstrip technology with step impedance method, that is by combining high impedance microstrip and low impedance microstrip with a certain length. As for designing HPF using the distribution method of short circuit stubs by adding via ground on each stub. The design of this filter uses Roger substrate RT 5880 with dielectric constant Îµr = 2,2 with thickness (h) = 0.508 mm. In this research it can be concluded that bandpass filter can be designed with lowpass and highpass filter incorporation method, although at the merging of highpass and lowpass structures is disturbed by each other, but overall design shows matching bandpass.